Online self-management interventions and their implications for chronically ill patients - Archer, Norman P.; McMaster eBusiness Research Centre (MeRC) (My University, 2012)
Direct medical care costs for chronic disease account for over 40% of Canadian healthcare expenditures, so the use of self-management to shift more healthcare responsibility to the chronically ill themselves is becoming a major consideration in controlling healthcare costs. Self-management interventions (SMIs) using online patient centred support can enable a collaborative approach that empowers patients to manage their own chronic illnesses, supported by their circle of care. This can include support in learning and supporting behaviours such as complying with prescribed medication and non-prescribed remedies; monitoring symptoms; lifestyle adjustments such as dietary change, alcohol restriction, and smoking cessation; exercise and weight loss; and related preventive activities (e.g. oral and body hygiene, sufficient rest, etc.). A critical issue is online SMI sustainability. This is not just financial viability and cost effectiveness, but motivating patients to adopt and then to continue using SMIs indefinitely to help reduce the risks associated with their chronic illnesses. This paper reviews the literature on online SMIs, including how they can be implemented in a sustainable manner, technology support for SMIs through personal health record systems and online fixed or mobile applications, and complexities that can arise from patient age-related issues.
23 p. ; Includes bibliographical references. ; "November 2012."
Keywords: Health self-management; Chronically ill patients; Online patient support; Sustainability; Age-related patient issues; Cognitive impairment